2015
DOI: 10.3944/aott.2015.14.0044
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of orthopedic publications originating from Turkey

Abstract: With the newly established universities, as well as training and research clinics, the approach of increasing number of orthopedics and traumatology clinics and specialists to scientific activities would be more fruitful in the light of these data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 20 publications
2
23
1
Order By: Relevance
“…Bibliometric analysis of the total number of orthopaedic articles over the last 10 years has consistently shown that the USA, UK, Germany, Japan and Korea have ranked amongst the countries with the highest publications . Country specific bibliometric analysis of orthopaedic publication rates have only been performed by Ireland and Turkey . These authors focused on the institution, individual authors, and distribution of these publications among journals.…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometric analysis of the total number of orthopaedic articles over the last 10 years has consistently shown that the USA, UK, Germany, Japan and Korea have ranked amongst the countries with the highest publications . Country specific bibliometric analysis of orthopaedic publication rates have only been performed by Ireland and Turkey . These authors focused on the institution, individual authors, and distribution of these publications among journals.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the vast growth of the scientific literature, an overview of the most relevant past publications has become more important than ever. In more recent years, bibliometric studies have therefore gained momentum and were subsequently published for fields as broad as surgery in general, 2 medical specialties, 3,4 anatomic regions, 5 surgical procedures, 6 geographic origin of studies, 7,8 and individual disease entities. 9 In the field of the human spine, two bibliometric studies have been published.…”
mentioning
confidence: 99%
“…GDP and GDP per capita are indicators of economic strength representing the value of all goods and services produced over a specific time period. 12 The lower the cost of producing a research paper per capita/GDP should be a direct indicator of a country's research productivity. When adjusting for GDP and GDP per capita, South Africa ranked in the lowest quarter.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Only Ireland and Turkey have specifically investigated their country's individual contribution to orthopaedic literature with a focus on the institution, individual authors and distribution of publications among journals. 12,13 However, the total number of publications may not account for economic discrepancies and population size. 11 In addition, the availability of funding would certainly result in higher publication output by countries with a larger population size and more powerful economies in particular when considering the economic realities of low income and developing countries.…”
Section: Introductionmentioning
confidence: 99%